Bromoacetic acid impairs mouse oocyte in vitro maturation through affecting cytoskeleton architecture and epigenetic modification. (1st December 2022) - Wang, Yong-Sheng; Zhang, Li-Dan; Zhou, Xv; Yang, Sheng-Ji; Ahmad, Muhammad Jamil; Ding, Zhi-Ming; Duan, Ze-Qun; Chen, Yang-Wu; Liu, Ming; Zhang, Shou-Xin; Liang, Ai-Xin; Hua, Guo-Hua; et al.
Abstract: As a major public health achievement, disinfection of drinking water significantly decreases outbreaks of waterborne disease, but produces drinking water disinfection by-products (DBPs) unfortunately. The haloacetic acids (HAAs) including bromoacetic acid (BAA), the second major class of DBPs, are considered as a global public health concern. BAA has been identified as cytotoxic, genotoxic, mutagenic, carcinogenic, and teratogenic in somatic cells. However, the toxic effects of BAA on oocyte maturation remain obscure. Herein, we documented that exposure to BAA compromised mouse oocyte maturation in vitro, causing blocked polar body extrusion (PBE). Meiotic progression analysis demonstrated that exposure to BAA induced the activated spindle assembly checkpoint (SAC) mediated metaphase I (MI) arrest in oocytes. Further study revealed that exposure to BAA resulted in the hyperacetylation of α-tubulin, disrupting spindle assembly and chromosome alignment, which is responsible for the activation of SAC. Besides, the organization of actin, the other major component of cytoskeleton in oocytes, was disturbed after BAA exposure. In addition, exposure to BAA altered the status of histone H3 methylation and 5 mC, indicative of the damaged epigenetic modifications. Moreover, we found that exposure to BAA induced DNA damage in a dose-dependent manner in oocytes. Collectively, our study evidenced that exposure to BAA intervened mouse oocyte maturation via disrupting cytoskeletal dynamics, damaging epigenetic modifications and inducing accumulation of DNA damage. Graphical abstract: Image 1 Highlights: BAA exposure significantly compromised oocyte maturation in mouse. BAA exposure disrupted cytoskeletal dynamics in mouse oocytes. BAA exposure caused SAC continuous activation and meiotic arrest. BAA exposure altered epigenetic modifications in mouse oocytes. BAA exposure induced DNA damage accumulation in mouse oocytes.